2021
DOI: 10.1177/0975087820987173
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the African Security Regime through a ‘Multiple-Speed’ Approach: Challenges and Prospect

Abstract: The past two decade has witnessed a nuanced approach to addressing the institutional and normative responses to Africa’s unending security challenges, particularly the African Union’s mandate to create the African Standby Force (ASF). The growing infeasibility of operationalising the ASF has thus stimulated the conception of the South African initiated African Capacity for Immediate Response to Crises (ACIRC). This article places the establishment of ACIRC within the theoretical concept of flexible integration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Some also believe that it might sound incorrect to describe the transformation as a failure as it is too early to judge (Dauda et al, 2021;Tieku, 2004). However, some agree that the transmutation from the OAU to the AU marked a critical phase in the linear trajectory of achieving collective security on the African Continent through several challenges that still remain (Fagbayibo, 2021;Joshua & Olanrewaju, 2017). Overall, suffice to note that at the time of the formation of the OAU, most African states were under colonial bondage and that the OAU drew its objectives from decolonized African states to confer African unity.…”
Section: Discussionmentioning
confidence: 99%
“…Some also believe that it might sound incorrect to describe the transformation as a failure as it is too early to judge (Dauda et al, 2021;Tieku, 2004). However, some agree that the transmutation from the OAU to the AU marked a critical phase in the linear trajectory of achieving collective security on the African Continent through several challenges that still remain (Fagbayibo, 2021;Joshua & Olanrewaju, 2017). Overall, suffice to note that at the time of the formation of the OAU, most African states were under colonial bondage and that the OAU drew its objectives from decolonized African states to confer African unity.…”
Section: Discussionmentioning
confidence: 99%
“…125which BabatundeFagbayibo (2021) accounts as African agency, quest for owning the narrative driven by African people Kassis et al (2021). confirmed that parents do not ignore their children's social and emotional well-being to the extent that BAL understand who they are, that Black identity symbolises beauty, boldness, robustness, power, elegance, devotion, loyalty and sophistication.…”
mentioning
confidence: 95%